Sociology - Giddens, Anthony; Sutton, Philip W. (Cambridge : Polity, 2011)
Anthony Giddens's 'Sociology' is paired up with the specially tailored and revised selection of key sociological works in 'Sociology - Introductory Readings'.
Includes bibliographical references and index.
Keywords: Sociology; Society